2021
DOI: 10.1088/1674-4527/21/11/292
|View full text |Cite
|
Sign up to set email alerts
|

LAMOST Time-Domain survey: first results of four K2 plates

Abstract: From Oct. 2019 to Apr. 2020, LAMOST performed a time-domain (TD) spectroscopic survey of four K2 plates with both low- and medium-resolution observations. The low-resolution spectroscopic survey acquired 282 exposures ( ≈ 46.6 h) over 25 nights, yielding a total of about 767 000 spectra, and the medium-resolution survey took 177 exposures ( ≈ 49.1 h) over 27 nights, collecting about 478 000 spectra. More than 70%/50% of low-resolution/medium-resolution spectra have signal-to-noise ratio higher than 10. We dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…In our Doppler shift measurements and plasma density/ temperature diagnostics, a Markov chain Monte Carlo (MCMC) analysis method was used to constrain and evaluate the multiparameter fitting results. This method can sample the posterior probability distributions of the fit results based on Bayesian statistics and has been extensively used by the astronomical community (e.g., Li et al 2019a;Chen et al 2020;Wang et al 2021b). The MCMC analysis method we used is the open-source code emcee (Foreman-Mackey et al 2013), which can be found in the Python package LMFIT (see Newville et al 2014).…”
Section: Appendix Mcmc Analysis Of Multiparameter Spectral Line Fitsmentioning
confidence: 99%
“…In our Doppler shift measurements and plasma density/ temperature diagnostics, a Markov chain Monte Carlo (MCMC) analysis method was used to constrain and evaluate the multiparameter fitting results. This method can sample the posterior probability distributions of the fit results based on Bayesian statistics and has been extensively used by the astronomical community (e.g., Li et al 2019a;Chen et al 2020;Wang et al 2021b). The MCMC analysis method we used is the open-source code emcee (Foreman-Mackey et al 2013), which can be found in the Python package LMFIT (see Newville et al 2014).…”
Section: Appendix Mcmc Analysis Of Multiparameter Spectral Line Fitsmentioning
confidence: 99%
“…Therefore, it balances the tradeoff between TPR and FPR and relies on specific science goals. For example, our low Λ model has been used in the LAMOST-TD survey (Wang et al 2021c) to prompt possible SB2 candidates. It serves as an aid parallel to manual inspection and works well.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with high-precision photometry from Kepler/K2 and TESS, it forms a valuable and sizable data set for time-domain research on this scientific goal (e.g., Pan et al 2020Pan et al , 2021Wang et al 2021aWang et al , 2021b. A subproject toward four K2 plates, namely, the LAMOST-TD survey (Wang et al 2021c), has led to the discovery of a subgiant with an undetected 1-3 M e companion (Yang et al 2021a). Minutecadence photometry is obtained for LAMOST MRS fields, as well to study short-period variables (Lin et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For a target of the MRS, there are two spectra within an exposure, including a blue-and a red-band spectrum. The blue and red cameras cover wavelength ranges from 4950-5350 Å and from 6300-6800 Å (Liu et al 2020;Wang et al 2021), respectively. The limiting magnitude is around G = 15 mag for targets of LAMOST-MRS (Liu et al 2020), while LAMOST-LRS has a limiting magnitude of r ∼ 18 mag (Luo et al 2015).…”
Section: Lamost Spectramentioning
confidence: 99%